2022
DOI: 10.2459/jcm.0000000000001411
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan reduces cardiac decompensation in heart failure with preserved ejection fraction: a meta-analysis

Abstract: BackgroundThe impact of sacubitril–valsartan on heart failure (HF) patients with preserved ejection fractions (HFpEF) is uncertain. The purpose of this meta-analysis was to explore the clinical advantages and safety of sacubitril–valsartan in patients with HFpEF.MethodsPubMed and Web of Science were searched without any restrictions from inception to 8 May 2022 to identify valuable articles. The studies that met the inclusion criteria were analyzed.ResultsFour trials, with a total of 7008 patients were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It can decrease mortality and the risk of hospitalization in patients with HF. [9,10] Liver dysfunction is prevalent in HF patients, so there has been growing interest in the relationship between the heart and the liver in HF. [11] Sacubitril/valsartan improves measures of liver function compared with enalapril.…”
Section: Discussionmentioning
confidence: 99%
“…It can decrease mortality and the risk of hospitalization in patients with HF. [9,10] Liver dysfunction is prevalent in HF patients, so there has been growing interest in the relationship between the heart and the liver in HF. [11] Sacubitril/valsartan improves measures of liver function compared with enalapril.…”
Section: Discussionmentioning
confidence: 99%
“…How important the duration of HF is has been evaluated in a recently published post hoc analysis of PARAGON-HF RCT [ 112 ], which reported that the longer the HF duration was, the higher the risk of HFH in the absence of significant variations in the effects of sacubitril/valsartan. Moreover, the highest benefit was reported in those subjects with long-standing HF.…”
Section: Evidence-based Medicine: Appropriateness Of Treatment and Pa...mentioning
confidence: 99%
“…More recently sodium glucose co-transporter 2 inhibitors (SGLT2i) have demonstrated efficacy in treatment of HFpEF reducing morbidity and mortality [ 7 ]. Moreover, recent meta-analysis including patients with HFpEF supports the beneficial effect of neurohormonal inhibitors, ACE inhibitors, angiotensin receptor inhibitors, and angiotensin receptor/neprilysin inhibitor (ARNi) on a composite outcome of death and HF hospitalizations [ 8 , 9 ].…”
Section: Epidemiologymentioning
confidence: 99%